Through the Lens of Postcolonial Theory: Establishing Global North-South Partnerships. Issue 5 (September 2019) - Healey-Walsh, Judith; Stuart-Shor, Eileen; Muchira, James
Abstract: AIM: This study used postcolonial theory as a critical lens to examine the factors that supported or hindered equitable partnership formation within an innovative international service-learning (ISL) program in nursing education. BACKGROUND: As ISL programs proliferate, ethical concerns have arisen as minimal attention has been given to both the host and visiting partners' experience and perceptions and how these impact partnership development and outcomes. METHOD: A hybrid intrinsic, instrumental, single embedded case study design, including observations, interviews ( n = 70), and document analysis, was used to analyze in depth varied partnerships within a US-Kenyan ISL program. RESULTS: Central themes of dispelling assumptions, making connections, revealing privilege, and sharing power emerged and formed a theoretical model, Establishing and Strengthening Partnerships. CONCLUSION: Attention needs to be given to preconceived assumptions, imbalances in privilege, and issues surrounding power and decision-making for equitable, impactful, partnership development. Leadership philosophy, style, and approach make a difference. Abstract : Supplemental digital content is available in the text.